The Ijazah Tradition in the 19th-20th Century Balkans - Idriz, Mesut (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Ijazah Tradition in the 19th-20th Century Balkans